2020
DOI: 10.3329/baj.v23i1.50114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphorus Levels on Growth and Yield of Four Lentil Varieties

Abstract: An adequate supply of phosphorus (P) is important for the proper growth and yield of lentil, particularly in poor fertile soil. As such an experiment was carried out to evaluate the effects of phosphorus (P) fertilizer application on growth, yield, and yield components of lentil at the agronomy research field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during 2013-201. Four lentil varieties (BARI Masur-4, BARI Masur-5, BARI Masur-6, and BARI Masur-7) and four levels of P (0, 20, 40 and 60 kg P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Significant and higher plant height was observed with application of phosphorus (50kg/ha) might be due to a sufficient quantity of phosphorus can stimulate biological activity. Similar findings have been reported by Sonet et al [11] in lentil. Further, higher plant height was observed with spacing (30cm×30cm) might be due to plant get sufficient space under wider spacing for light, air and nutrition for better growth and development.…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…Significant and higher plant height was observed with application of phosphorus (50kg/ha) might be due to a sufficient quantity of phosphorus can stimulate biological activity. Similar findings have been reported by Sonet et al [11] in lentil. Further, higher plant height was observed with spacing (30cm×30cm) might be due to plant get sufficient space under wider spacing for light, air and nutrition for better growth and development.…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…The application of 90 kg P2O5 ha -1 resulted in the highest number of main and secondary branches, with values of 5.93 and 10.26, respectively while minimum values in control (3.61 and 6.40, respectively). Kumar et al [17], and Sonet et al [18] reported similar results. The data (Table -1) indicate that the number of primary and secondary branches per plant recorded at harvest increased significantly with zinc application in the crop.…”
Section: Number Of Branches Per Plantmentioning
confidence: 59%
“…The plant height exhibited a significant increase, rising from 46.19 cm under normal conditions to 53.71 cm when subjected to a dosage of 90 kg [17], and Sonet et al [18].…”
Section: Plant Heightmentioning
confidence: 90%
“…Besides, phosphorus application stimulates crop growth along with dry matter production, leading to improved photosynthate translocation and sink development resulting in higher 100 seed weight (Karnavat et al, 2018). It also boosts nitrogenase activity of root nodules and prolongs crop maturity, having an impact on test weight in pulses (Sonet et al, 2020). Ram and Dixit (2001) and Hussen et al (2020) also observed higher test weight @ 60 kg P 2 O 5 ha -1 .…”
Section: Discussionmentioning
confidence: 93%